2005
DOI: 10.1590/s0101-81752005000300021
|View full text |Cite
|
Sign up to set email alerts
|

Imaturos de Culicidae (Diptera) encontrados em recipientes instalados em mata residual no munícipio de Londrina, Paraná, Brasil

Abstract: Fragmentos de mata na área urbana ou periurbana podem ser locais favoráveis a procriação de Culicidae. Esse trabalho teve como objetivo levantar as espécies de culicídeos que utilizam criadouros artificiais, suas coexistência e as flutuações populacionais em uma reserva de mata localizada em Londrina - PR. Realizou-se coletas quinzenais de outubro de 1995 a setembro de 1996 em pneus e internódios de bambu armadilha que foram instalados ao nível do solo e outros internódios instalados a 2 m de altura. Coletou-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 31 publications
3
33
0
6
Order By: Relevance
“…ferox abundance decreasing in the advance of sets, similar to observed by Consoli and Oliveira (1994). Aedes species found in this study are adapted to anthropogenic environments and they are found in several artificial breeding sites (Lopes, 1997;Zequi et al, 2005). While Hg.…”
Section: Discussionsupporting
confidence: 87%
“…ferox abundance decreasing in the advance of sets, similar to observed by Consoli and Oliveira (1994). Aedes species found in this study are adapted to anthropogenic environments and they are found in several artificial breeding sites (Lopes, 1997;Zequi et al, 2005). While Hg.…”
Section: Discussionsupporting
confidence: 87%
“…durhami showed population increases in rainy months. Zequi et al (2005) also reported greater abundances of Li. durhami during the summer due to the greater availability of larval habitats and Guimarães et al (2000) found the greatest incidence of this species in January and April.…”
Section: Discussionmentioning
confidence: 92%
“…The breeding sites of C. eduardoi are often found next to human settlements (Lopes 1997b, 1999, Vezzani et al 2001 and some authors emphasize the ability of this mosquito to adapt to anthropogenic environments (Lopes 1997a, Zequi et al 2005, with both of these features having important epidemiologically implications. Our study contributes to the limited knowledge of the biology of C. eduardoi and could be useful to understand its population dynamic.…”
Section: Resultsmentioning
confidence: 99%